CLASH DETECTION ANALYSIS OF RSIA BUILDING CONSTRUCTION USING AUTODESK REVIT AND NAVISWORKS - I Putu Ari Sanjaya; I Gusti Agung Adnyana Putera; Putu Ira Pramesti Wiraningsih; The Nikolaus Ferrer (Jurnal Ilmiah Teknik Sipil, 2025)
Clashes between objects in construction projects often lead to delays, increased costs, and rework due to a lack of coordination between disciplines and the limitations of traditional clash detection technologies. This study evaluates the effectiveness of implementing clash detection based on Building Information Modeling (BIM) using Autodesk Revit and Navisworks in reducing rework, additional costs, and project duration. The research adopts a quantitative method using secondary data, including 3D models, time schedules, and Unit Price Analysis. The analysis identified a total of 964 clashes, consisting of 274 structure-MP clashes, 603 architectural-MP clashes, and 87 structure-architectural clashes. The implementation of clash detection resulted in a rework reduction of 0.34% and a total cost saving of 4.63%, which includes savings in structural work (0.08%), architectural work (7.76%), and mechanical-plumbing work (0.06%). Avoided rework includes the demolition of 4.93 m³ of concrete, 70.81 m² of walls, 1051.11 m² of ducting relayout, and 1.05 m of pipe relocation. Additionally, the potential time saving is estimated at 41.7 days or 7.79% of the total project duration.